Workplace based learning in district health leadership and management strengthening: A qualitative evidence synthesis - Kiarie, Grace (Department of Public Health and Family Medicine, 2024)
Effective leadership and management has been identified as a critical foundation to enable health systems to respond adequately to their population needs. The changing nature of low-and middleincome countries' health systems in the midst of resource scarcity and a high disease burden, has placed learning as a key factor for health system reform and transformation, with workplace based learning (WPBL) as contributing to this learning process. This qualitative evidence synthesis (QES) used the ‘best fit' framework approach to synthesize evidence on WPBL, to identify and analyse how WPBL works to support and impact (or not) leadership and management development in the district health system. Findings from qualitative studies, mixed-methods and quantitative studies were synthesized and conclusions drawn from the data. The QES sought to answer the research question: ‘What forms of workplace based learning support leadership and management development and how does it impact district health leadership and management strengthening?' Four electronic databases were used to search for empirical studies and published grey literature. Twenty-four articles were included in the synthesis. The findings reveal that over the last decade, WPBL has received consideration as an approach for leadership and management development. However, while the WPBL interventions differed in the type and nature of the intervention, as well as the length of delivery of each intervention, there was no evidence that pointed to which strategy had a greater influence than others on strengthening district health leadership and management. Furthermore, the synthesis demonstrates the need for a focus on sustainability and institutionalization of interventions, including the need to integrate WPBL interventions in health systems, and offering elements of WPBL through national or regional institutions while ensuring flexibility of WPBL design and delivery.